Metrics, scales, and correlates of intraspecific variation in hypoxia tolerance in fishes - Babin, Courtney H.; Rees, Bernard B. (Frontiers in Fish Science, 2025)
The extent of aquatic hypoxia (low dissolved oxygen) has increased in recent times and now threatens aquatic habitats worldwide. Here, we review intraspecific variation in hypoxia tolerance in fish on various scales: geographic variation among populations; variation among genetic strains; variation due to laboratory acclimation; and variation among individuals coming from a given population and having similar exposure history. Metrics of hypoxia tolerance include the oxygen level below which the costs of maintenance can no longer be met by oxygen uptake from the environment; the time or oxygen level at which aquatic surface respiration is conducted; and the time or oxygen levels at which fish lose the ability for coordinated movement. There is great diversity in the range of intraspecific hypoxia tolerance and its association with potential underlying morphological, physiological, and genetic correlates. We advocate for greater standardization of experimental design, enhanced data reporting, and development and validation of new metrics of hypoxia tolerance. With greater understanding of intraspecific variation in hypoxia tolerance, it might be possible to predict which populations, strains, or individuals will fare better during hypoxic episodes; mitigate the effects of low oxygen on fishes; and design breeding protocols to enhance the hypoxia tolerance of fishes.